Utilization of ATP and Its Derivatives as an Index of Freshness of Nila (Oreochromis niloticus) During Storage - Djagal W Marseno; Sudarmanto Sudarmanto; Retno Indrati (Indonesian Association of Food Technologists, 1999)
The role of a reliable and reproducible, index of fish freshness, is important. The objective of this research was to examine the utilisation of ATP and its derivatives (expressed as K-value) as an index offish freshness using Nila (Oreochromis niloticus) as a model of study. K-value is [(Inosine + Hypoxanthine) / (ATP + ADP + AMP + IMP + Inosine + Hypoxanthine)] x 100%. Live fish were killed, packed individually using polyethylene bag and stored at 4 and 28°C. At defined time, some fishes were examined their ATP and its breakdown products using a reverse phase HPLC system. The results showed that ATP, ADP and AMP were degraded rapidly and disappeared within 12 ho urs. Degradation of IMP in the samples stored at 4°C was slower than those of samples stored at 28°C. Interestingly, the accumulation of Inosine occurs only in the samples stored at 28°C while the accumulation of Hypoxanthine occurs only in the samples stored at 4